PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL PADA KINERJA PERAWAT RUMAH SAKIT ISLAM SITI AISYAH MADIUN - Murtiningsih Murtiningsih (Universitas Muhammadiyah Surakarta, 2015)
This study aims to determine the effect of leadership traansformasional test theperformance of which is mediated by two variables: trust in leaders and job satisfaction. This research is a quantitative empirical research with cross sectional study design. These samples included 111 respondents. Hypothesis testing using regression analysis with the approach of Baron and Kenny (1986). Validity and reliability of the research questionnaire value of KMO Measure of Sampling Adequacy (MSA) in this study amounted to 0.835 continued test and a valid and reliable factor. The results showed that transformational leadership significant and positive impact on performance. The variables of transformational leadership have a significant effect on the performance, variable trust in leaders and job satisfaction variables have a role as a mediating variable.